Orthographies in Early Modern Europe - Baddeley, Susan; Voeste, Anja (2012)
This volume provides, for the first time, a pan-European view of the development of written languages at a key time in their history: that of the 16th century. The major cultural and intellectual upheavals that affected Europe at the time - Humanism, the Reformation and the emergence of modern nation-states - were not isolated phenomena, and the evolution of the orthographical systems of European languages shows a large number of convergences, due to the mobility of scholars, ideas and technological innovations throughout the period.